Orthogonal Projections and the Perturbation of the Eigenvalues of Singular Pencils (Journal of Computational Mathematics, 2018)
In this paper we obtain a Hoffman-Wielandt type theorem and a Bauer-Fike type theorem for singular pencils of matrics. These results delineate the relations between the perturbation of the eigenvalues of a singular diagonalizable pencil $A-λB$ and the variation of the orthogonal projection onto the column space $\mathcal{R} \Bigg( \begin{matrix} A^H \\ B^H  \end{matrix} \Bigg)$.